The science and physiology of flexibility and stretching. Implications and applications in sport performance and health - Behm, D. G. (Routledge, 2019)
Stretching is a fundamentally important part of sport and exercise, playing a role in improving performance, and preventing injury and rehabilitation, but its scientific underpinnings have, to this point, been overlooked in book publishing. The Science and Physiology of Flexibility and Stretching is the most up-to-date and comprehensive book to cover the underlying physiology and psychology of stretching, critically assessing why, when, and how we should stretch, as well as offering a highly illustrated, practical guide to stretching exercises.